Review of nonlinear modelling parameters and acceptance criteria in ASCE 41 for seismic evaluation and upgrading of steel structures in Canada - Kim, Taeyong; Kwon, Oh Sung; Acosta, Joaquín; Fathi-Fazl, Reza; Fazileh, Farrokh; Cai, Zhen (Canadian Journal of Civil Engineering, 2023)
The seismic resilience of structures can be quantified through rigorous seismic assessment. Because no detailed guideline is available for nonlinear modelling parameters and the corresponding acceptance criteria for the seismic evaluation and upgrading of steel structures in Canada, the structural commentary of the National Building Code of Canada suggests using ASCE 41, which has been adopted as a standard for seismic evaluation and retrofit of buildings in the United States (U.S.). However, because the steel design standards in Canada and the U.S. are different, their applicability to steel structures in Canada needs to be investigated. To this end, this paper critically reviews the nonlinear modelling parameters and acceptance criteria, and then recommends whether these values need to be revised or are adopted as is for the seismic evaluation and upgrading of steel structures in Canada. A numerical example of a steel moment-resisting frame is presented to demonstrate the recommended parameters being used for seismic evaluation.
Keywords: Acceptance criteria; Modeling parameters; Non-linear modelling; Performance:level; Seismic assessment; Seismic evaluation; Seismic resilience; Seismic upgrading; Structural performance; Structural performance level; acceptance criteria; nonlinear modelling; seismic evaluation and upgrading; steel structures; structural performance levels